Penalización de la dosis personal: “irrupción en el fuero interno de la persona - Carreño Blanco, Luz Elena; Páez Páez, María Angélica; Mariño Guío, Diana Catalina (Uptc, 2012)
After the enactment of Law 1453 of 2011 (Public Security Act), article 11, and the Legislative Act of 2009 that amends article 49 of Colombian Constitution, has emerged the question about if the “dose for personal use”, which is instituted in article 2 of Law 30 of 1986, must be penalized. There has indeed inferred the impossibility, since that article which decriminalized it, has not been abolished, and from the argumentative point of view, not all interference of the State in the conscience of the person through the Criminal Law is legitimate, if the conduct does not violate rights of others.